STAFILO-STREPTODERMIYA AS REASON OF ORIGIN PHLEGMONS OF MAXILLUFACIAL AREA FOR CHILDREN - Tkachenko, P.I.; Ischeykin, K.E.; Belokon, S.A.; Gurziy, E.V. (World of Medicine and Biology, 2010)
In the article reasons of origin of dermatogenics inflammatory processes of maxillufacial area are considered for children, the results of clinical research of patients are presented with this pathology on the example of inspection and treatment of child with the phlegmon of maxillufacial area, developing on a background stafilo-streptoderma. The ways of prophylaxis of development of dermatogenics inflammatory processes of maxillufacial area are set for children.